A Study on Zhang Xichun’s Life and Contributions to Converging and Connecting Chinese and Western Medicine - Hailong Zhai, Zhongjuan Li, Hui Tu, Li Min (Forest Chemicals Review)
To explore Zhang Xichun’s life, contributions to converging and connecting Chinese and western medicine, references and literatures related to Zhang Xichun were collected by searching Pubmed, cnki, bing and then were studied. Zhang Xichun (1860-1933) was a representative figure of the “school of integration of traditional Chinese medicine (TCM) and Western medicine”. In 1909, he finished the first three volumes of Essays on Medicine Esteeming the Chinese and Respecting the Western (his famous book) and was a famous physician in modern China. In 1912, he was hired as a major medical officer. His good medical ability was gradually well-known. In 1918, Zhang Xichun was recruited as the hospital chief of Lida Hospital, the first TCM hospital in Chinese history. He thought that TCM and Western medicine should study mutually. He said “Converging and connecting TCM and western medicine to form one.” He tried to integrated Chinese and Western medicine on physiology, pathology, and pharmacology. He invented several new formulas combining TCM herbs and western medicine and a lot of good TCM formulas. He established Letter Communication School of TCM. Zhang Xichun tried to explain Western medicine with the theories of TCM and firstly started therapy of integrated Chinese and Western medicine. He made tremendous contributions to combining TCM and western medicine. His innovative and aggressive courage is worth of our tribute and learning.